The prevalence of genital ulcer diseases and HIV infection among male STD patients at STD clinic of Northern Thailand, 1994 - Pongtong, Jitrat
To assess the prevalence of human immunodeficiency virus (HIV) infection among with males STD, 195 male STD who patients attended clinics for sexually tramitted diseases in Northern Thailand, between August 1, 1994 to February 10, 1995, were interviewed by counsellors. All subjects were diagnosed based on physician's diagnosis and laboratory investigation. They were classified according to the presence or absence of genital ulcer disease (GUD). Under the GUD group were those patients with syphilis, genital herpes, chancroid, and lymphogranuloma venereum LGV). The non GUD group consisted of those patients with gonorrhea, non-gonorrhea, genital wart, fungal infection, secondary syphilis, and scabies. The subjects underwent HIV blood testing anonymously. HIV infection was defined as two Enzyme Link Immunosorbent Assay (ELISA) positive results and confirmed by Western (WB).Twenty eight percent (55/195) of the subjects were seropositive for HIV. The prevalence of HIV infection among men with GUDs is 52(29/55) and 18(26/140) were without GUDs.The crude odds ratio of GUD was 5.67. After controlling for history of genital herpes and condom use during vaginal sex with prostitutes within the past 6 months, the adjusted odds ratio was 5.9. This study suggests that GUD is a strong risk factor for HIV infection.A potentially useful intervention method to prevent sexually transmitted diseases regarding genital ulcer diseases, including HIV infection, is to promote the use of condoms and to encourage safer sexual practices.